Conflict in Ukraine: Inflections Points after the Zeitenwende and Article 51 of the Charter of United Nations - Sebastian Kornhauser (Groningen Journal of International Law)
The world stands at a juncture of violence where unipolarity ends and multipolarity begins. Manifestations of Western hegemonism, incremental NATO eastward expansion, the proliferation of US military bases overseas and the unilateral resort to force in ways that transgressed the constraints contained in Article 51 of the UN Charter were instrumental in provoking Russia into aggression. The US, as a pioneer in interpreting the right to self-defence widely to include anticipatory and pre-emptive self-defence, resulted in disastrous consequences in, inter alia, Iraq and Afghanistan. US hegemonism became offensive to the non-Western world. The Russian invasion of Ukraine, partially in reliance on collective self-defence in Article 51, partially on mutual assistance contained in Articles 4 common to the Treaties of Friendship, Cooperation, and Mutual Assistance with both Donbas Republics and partially in defiance to the collective West, is geographically reciprocal. A synallagmatic wrong parallel to how the US acted in Iraq and Afghanistan on an ‘if you can break international law, then so can we’ basis.